Rozwijanie komunikacji funkcjonalnej w terapii dzieci z zaburzeniami ze spektrum autyzmu - Sławek, Jolanta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
In the article, the author presents issues related to developing functional communication in both verbal and non-verbal children with autism spectrum disorders. The most important strategies that can be used when working with ASD children are discussed, such as claiming an object or an action, making a choice or asking questions. At the same time, the author underlines the importance of early intervention in small children with autism which may improve their abilities when it comes to learning, playing and communicating as well as their social skills. It may also help in the area of problematic behaviour, such as fits of anger or aggression. Teaching an ASD individual to communicate in a functional way equips them with a tool for expressing their needs and emotions. It also influences their relations with other people, allowing them to fully participate in social life.